First record of three species of "Pythium" from Moroccan waters - El Androusse, Amal; El Aissami, Aicha; Rahouti, Mohamed; Lahlou, Houria; Ben Abdellah, Samira; Seigle Murandi, Françoise (Universidad de Málaga, Servicio de Publicaciones, 2007)
First record of three species of Pythium from Moroccan waters. Species of Pythium, including P.torulosum, P.catenulatum and P. "Group F", isolated from dam near Rabat city (capital of Morocco) in northern Africa, are described. Taxonomic and morphological details of the fungi are discussed. This work is the first report of these species from Moroccan waters.

Primeras citas de tres especies de Pythium para Marruecos. Se describen especies de Pythium, incluyendo P. torulosum, P. catenulatum y P. "Group F", aislados cerca de la ciudad de Rabat (Marruecos) en el norte de Africa. Se discuten detalles taxonómicos y morfológicos del hongo. Este trabajo es la primera refencia de estas especies en aguas de Marruecos.